2012
DOI: 10.1016/j.jhep.2011.11.018
|View full text |Cite
|
Sign up to set email alerts
|

A dual role for hypoxia inducible factor-1α in the hepatitis C virus lifecycle and hepatoma migration

Abstract: Background & AimsHepatitis C virus (HCV) causes progressive liver disease and is a major risk factor for the development of hepatocellular carcinoma (HCC). However, the role of infection in HCC pathogenesis is poorly understood. We investigated the effect(s) of HCV infection and viral glycoprotein expression on hepatoma biology to gain insights into the development of HCV associated HCC.MethodsWe assessed the effect(s) of HCV and viral glycoprotein expression on hepatoma polarity, migration and invasion.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
67
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 38 publications
10
67
1
1
Order By: Relevance
“…4A), HRE activity (see Fig. S2 in the supplemental material) was similar between HCV-and noninfected cells at early hours p.i., whereas at 72 h p.i., an ϳ2-fold increase was detected in infected cells, in agreement with studies (42)(43)(44) showing HIF-1 activation at late stages of HCV infection.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…4A), HRE activity (see Fig. S2 in the supplemental material) was similar between HCV-and noninfected cells at early hours p.i., whereas at 72 h p.i., an ϳ2-fold increase was detected in infected cells, in agreement with studies (42)(43)(44) showing HIF-1 activation at late stages of HCV infection.…”
Section: Resultssupporting
confidence: 90%
“…S6 in the supplemental material). Notably, HIF-1␣ activation from HCV at late stages of viral infection has been reported under normoxia and has been linked to mitochondrial dysfunction and oxidative stress caused by HCV proteins (42)(43)(44). In agreement with these studies, we also detected an increase in HIF-1␣ activation, but only 72 h p.i.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further study is necessary to verify the transition from EMT to an immortalized or transformed phenotype. A different report (42) suggested that the E-cadherin level is reduced in HCV glycoprotein-expressing HepG2 cells, and HCV infection promotes snail and twist expression in both Huh7.5 cells and primary human hepatocytes. However, those authors failed to observe any morphological fibroblast features of HCV-infected or glycoprotein-expressing hepatoma cells, possibly due to the partial de-differentiation process in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…Notable was the upregulation of HIF-α (EPAS1 and HIF1A), which led to the up-regulation of growth factors (TGFB2, TGFB3, VEGFA, PDGFB) and glucose transporter SLC2A1/GLUT1. Previous studies have shown that the expression of HCV protein activates HIF-1 by normoxic stabilization of its α subunit (HIF-α), resulting in increased expression of HIFcontrolled genes, many of which are involved in tumor growth and metastasis, such as VEGF and TGF-β [53][54][55].…”
Section: Discussionmentioning
confidence: 99%